Challenging Radiofrequency Catheter Ablation of Idiopathic Ventricular Arrhythmias Originating From the Left Ventricular Summit Near the Left Main Coronary Artery. (October 2016) - Yamada, Takumi; Doppalapudi, Harish; Litovsky, Silvio H.; McElderry, H. Thomas; Kay, G. Neal
Abstract : Background—: Radiofrequency catheter ablation (RFCA) of idiopathic ventricular arrhythmias (VAs) originating from the basal portion of the left ventricular (LV) summit, which is divided from the apical LV (A-LV) summit by the great cardiac vein (GCV), is challenging. This study investigated the efficacy of RFCA and electrocardiographic and electrophysiological characteristics of these VAs. Methods and Results—: Forty-five consecutive patients with symptomatic idiopathic LV summit VAs were studied. RFCA was successful within the main trunk of the GCV in 16 patients and within a branch of the GCV traversing the basal LV (B-LV) summit in 7. Transpericardial RFCA was successful on the epicardial surface in the A-LV summit in 6 patients and was abandoned in 14 with the B-LV summit VAs because of the close proximity to the coronary arteries and thick fat pads. RFCA was successful at the aortomitral continuity in 3 patients (2 with a failed transpericardial RFCA), and left coronary cusp in 1. The RFCA success rate of the A-LV summit VAs including the GCV VAs was 100% (22/22), whereas that of the B-LV summit VAs was 48% (11/23). The B-LV summit VAs could be differentiated from the A-LV summit VAs by left bundle branch block pattern, QRS duration ⩽175 ms, precordial transition ≥V1, and maximum deflection index of ≥0.55. Conclusions—: This study revealed that ≈50% of the B-LV summit VAs could be eliminated by a direct approach through a GCV branch running below the proximal left coronary arteries and a remote approach from the adjacent endocardial sites.